Between Sharia Maqasid Index and Human Development Index: Which One is Happier? - Nur Hajrina; Wahyu Jatmiko (Media Syari'ah, 2020)
This research aims to find a more precise composite measurement format (index) in quantifying the ultimate achievement of human existence, which is happiness, in Organization of Islamic Cooperation (OIC) countries. Up until now, Human Development Index (HDI) is considered to be sufficiently representing the measure of human well-being. However, Easterlin (1974) argues that higher welfare does not always imply to higher happiness. Blanchflower and Oswald (2005) prove the statement of Easterlin (1974) by demonstrating the paradox between HDI level and happiness in Australia. Further, the measure of HDI is said to be less representative in reflecting happiness as it has not yet incorporated the element of religiosity. Thus, several of the new composite measures of well-being in Muslim countries have been proposed, one of them is Sharia Maqasid Index constructed by Ali and Hasan (2014). This research attempts to make comparison between HDI and Sharia Maqasid Index and to decide which of the two indices gives the best measure of human happiness. The authors employ Ordered Logit method and use data taken from World Value Survey along the period of 1999-2009 to measure happiness as in Leigh and Wolfers (2006), as well as to measure Sharia Maqasid Index as in Ali and Hasan (2014). Findings of this research can benefit the government of OIC countries to determine a more precise index as a benchmark to set more appropriate public policies.